2022
DOI: 10.3390/polysaccharides3020023
|View full text |Cite
|
Sign up to set email alerts
|

Low-Denaturazing Glucose Oxidase Immobilization onto Graphite Electrodes by Incubation in Chitosan Solutions

Abstract: In this work, glucose oxidase (GOx) has been immobilized onto graphite rod electrodes through an assisted-chitosan adsorption reaching an enzyme coverage of 4 nmol/cm2. The direct and irreversible single adsorption of the Flavine Adenine Dinucleotide (FAD) cofactor has been minimized by electrode incubation in a chitosan (CH) solution containing the enzyme GOx. Chitosan keeps the enzyme structure and conformation due to electrostatic interactions preventing FAD dissociation from the protein envelope. Using chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…[43][44][45] Carbon black (Nouryon, Ketjenblack EC-600JD), a type of conductive nanofiller, was infused with the thermoplastic polyurethane to improve the mechanical and electrical characteristics without losing biocompatibility, [53] although a detailed biocompatibility study was not performed. However, carbon black has already been used for biocompatible strain sensors and flexible bioelectrodes, [50,51] and the one used in this study showed high cell viability (100%) at a concentration of 32.5 µg mL −1 during an in vitro cytotoxicity study. [52] Additionally, as there is no evidence that the CSMP composite is nontoxic, an in vitro cytotoxicity test was performed (according to ISO 10993-5:2009 Biological Evaluation of Medical Devices -Part 5).…”
Section: Fabrication Methodsmentioning
confidence: 83%
“…[43][44][45] Carbon black (Nouryon, Ketjenblack EC-600JD), a type of conductive nanofiller, was infused with the thermoplastic polyurethane to improve the mechanical and electrical characteristics without losing biocompatibility, [53] although a detailed biocompatibility study was not performed. However, carbon black has already been used for biocompatible strain sensors and flexible bioelectrodes, [50,51] and the one used in this study showed high cell viability (100%) at a concentration of 32.5 µg mL −1 during an in vitro cytotoxicity study. [52] Additionally, as there is no evidence that the CSMP composite is nontoxic, an in vitro cytotoxicity test was performed (according to ISO 10993-5:2009 Biological Evaluation of Medical Devices -Part 5).…”
Section: Fabrication Methodsmentioning
confidence: 83%